Persistent mullerian duct syndrome in a patient with bilateral cryptorchid testes with seminoma - Shrinivasan Chamrajan; Nidhi H Vala; Jatin R Desai; Niraj N Bhatt (Wolters Kluwer Medknow Publications, 2012)
Persistent mullerian duct syndrome (PMDS) is a rare form of male pseudohermaphroditism in which mullerian duct derivatives are present in an otherwise normally differentiated 46 XY male. We report a case of a 33-year-old male with PMDS operated for postchemotherapy seminoma. A diagnosis of PMDS was made on subsequent histopathological evaluation.